2007
DOI: 10.1177/0020764007082344
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Social Network Diversity and Perceived Social Support After Psychiatric Hospitalization: Results From a Longitudinal Study

Abstract: Social disintegration in the course of mental illness that is found in some studies has no equivalent in our study in what concerns network diversity and perceived support. According to our results, characteristics of vocational and economic integration are of much greater relevance, as they enhance or hinder access to social participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
(84 reference statements)
2
19
0
6
Order By: Relevance
“…The findings showed that family members were the main source of supportive contacts and that few relied on staff in that sense, which confirms previous studies Muller, Nordt, Lauber, & Rössler, 2007). The results of the specific items showed that quite a few participants lacked close contacts, suggesting that attention to the need for social support in the target group is highly warranted.…”
Section: Discussionsupporting
confidence: 87%
“…The findings showed that family members were the main source of supportive contacts and that few relied on staff in that sense, which confirms previous studies Muller, Nordt, Lauber, & Rössler, 2007). The results of the specific items showed that quite a few participants lacked close contacts, suggesting that attention to the need for social support in the target group is highly warranted.…”
Section: Discussionsupporting
confidence: 87%
“…Female mentally ill are less socially isolated and more likely to be cohabiting and to have children (Müller et al, 2007). Higher male substance use and lower rates of depression were also confi rmed (Afi fi , 2007).…”
Section: Men and Women In 2006mentioning
confidence: 95%
“…Specifically, the connections among actors, centrality of the leader among the connections, density of the connections between actors in the leader's network, embeddedness of the relationships between actors, the range of connections within the network (individuals that are not interconnected to one another), network stability, and network size are proposed by the authors to all be related to team outcomes such as performance, and leader emergence and influence. Additionally, other research indicates that the diversity of actors within a network (Müller, Nordt, Lauber, & Rössler, 2007) may influence group processes ultimately related to the emergence of collective leadership.…”
Section: Leader Networkmentioning
confidence: 99%